Trading relations between tongue-body raising and lip rounding in production of the vowel /u/: a pilot "motor equivalence" study - Perkell, J S; Matthies, M L; Svirsky, M A; Jordan, M I (The Journal of the Acoustical Society of America, 1993)
Articulatory and acoustic data were used to explore the following hypothesis for the vowel /u/: The objective of articulatory movements is an acoustic goal; varying and reciprocal contributions of different articulators may help to constrain acoustic variation in achieving the goal. Previous articulatory studies of similar hypotheses, expressed entirely in articulatory terms, have been confounded by interdependencies of the variables being studied (e.g., lip and mandible displacements). One case in which this problem may be minimized is that of lip rounding and tongue-body raising (formation of a velo-palatal constriction) for the vowel /u/. Lip rounding and tongue-body raising should have similar acoustic effects for /u/, mainly to lower F2. In multiple repetitions, reciprocal contributions of lip rounding and tongue-body raising could help limit F2 variability for /u/; thus this experiment looked for complementary covariation (negative correlations) in measures of these two parameters. An electro-magnetic midsagittal articulometer (EMMA) was used to track movements of midsagittal points on the tongue body, upper and lower lips, and mandible for large numbers of repetitions of utterances containing /u/. (Interpretation of the data was aided by results from area-function-to-formant modeling.) Three of four subjects showed weak negative correlations, tentatively supporting the hypothesis; a fourth showed the opposite pattern: positive correlations of lip rounding and tongue raising. The results are discussed with respect to ideas about motor equivalence, the nature of speech motor programming, and potential improvements to the paradigm.